MAQᾹṢID AL-QUR’ᾹN AYAT NAFKAH KEPADA ISTRI PERSPEKTIF ṢIDDĪQ HASAN KHAN DALAM KITAB FATḤ AL-BAYᾹN FĪ MAQᾹṢID AL-QUR’ᾹN - Abdullah Fahrur Rosi; Mohammad Farah Ubaidillah; Lizamah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
The issue of spousal maintenance (nafqa) remains a persistent source of domestic conflict within Muslim families, frequently contributing to marital breakdown and divorce. This study critically examines Ṣiddīq Ḥasan Khān’s conception of the husband’s obligation of maintenance as articulated in Fatḥ al-Bayān fī Maqāṣid al-Qur’ān, situating his exegetical position within a maqāṣid al-Qur’ān framework as developed by Maḥmūd Shaltūt. Rather than approaching maintenance solely as a juristic obligation, this article seeks to uncover the ethical and socio-moral rationales underlying Qur’anic injunctions on financial responsibility within marriage. Employing a qualitative, library-based research design, the study conducts a thematic analysis of key Qur’anic passages on maintenance—Qur’ān 2:233, 2:241, 4:5, 4:34, and 65:6–7—drawing on primary sources including the Qur’ān, Fatḥ al-Bayān, and Shaltūt’s Ilā al-Qur’ān, supported by relevant secondary literature in Qur’anic exegesis and Islamic family law. The findings demonstrate that Ṣiddīq Ḥasan Khān conceptualizes maintenance as the husband’s fundamental and continuous responsibility, encompassing provision of food, clothing, and housing in accordance with the husband’s financial capacity and prevailing social norms. This obligation persists under specific circumstances, such as during the ‘iddah period and pregnancy, reflecting a protective orientation toward women’s rights. From a maqāṣid al-Qur’ān perspective, maintenance emerges not merely as a legal prescription but as a moral commitment aimed at upholding justice, sustaining marital harmony, and securing broader social welfare. This study contributes to contemporary Qur’anic family law scholarship by integrating classical exegetical insights with a maqāṣid-oriented reading, offering a more ethically grounded and context-sensitive understanding of spousal maintenance in the Qur’ān.